Pathways to genetic parenthood for same-sex couples - Murphy, F. (Journal of medical ethics, 2018)
Researchers are pursuing various ways to synthesise human male and female gametes, which would be useful for people facing infertility. Some people are unable to conceive children with their partner because one of them is infertile in the sense of having an anatomical or physiological deficit. Other people—in same sex couples—may not be individually infertile but situationally infertile in relation to one another. Segers et al have described a pathway towards synthetic gametes that would rely on embryonic stem cells, rather than somatic cells. This pathway would be advantageous, they say, for same-sex couples even though it would not offer those couples 50%-50% shared genetics in their children but only 50%-25%. It is unclear, however, why this approach should be preferred morally speaking since it represents a falling off from the kind of shared genetics in children that are functionally a gold standard in parents' expectations generally. Despite raising concerns about whether genetic relatedness is necessary or sufficient as a condition of parental interest in children, Segers et al cede the sociocultural importance of that standard. If so, same-sex couples seem entitled to press a case for some measure of research priority that would offer the same level of access to that social good as everyone else.